Komunikasi Ritual Obiyem pada Etnis Tamil Hindu di Kota Medan - Ratna Sari Puspa; Suzy Azeharie (Koneksi, 2020)
The Tamil Hindu ethnic community is spread across Indonesia, the majority live in Medan North Sumatra. Obiyem ritual is a religious activity believed by the Tamil Hindu ethnic community. The ritual has existed since the time of Bharatayudha and it is believed to eliminate bad karma for anyone who participates and performs the ritual. This ritual also obliges the devotees to make offerings to the Gods and Goddesses as a form of gratitude for giving abundance, maintain and protecting the universe. With the existence of ritual communication, the Tamil Hindu ethnic community in Medan can communicate and relate to the creator through the Obiyem ritual. This tradition is still carried out by the Tamil Hindu ethnic community to this day. The purpose of this study is to find out how the ritual communication is at the ceremony to the Tamil Hindu ethnic in Medan and what preparations are needed when the ritual is performed. Theories used in this research are communication theory, ritual communication and transcendental communication.The research method used was a phenomenological method with a qualitative descriptive approach. The data were obtained from in-depth interviews with three sources who understood about the ritual of Obiyem. The conclusion of this study is the ritual of Obiyem is a media used to communicate between humans and the Creator so that all bad karma is eliminated. It is also strengthen the relationship of Tamil Hindu ethnic society.Masyarakat etnis Tamil Hindu di Indonesia mayoritas berada di kota Medan, Sumatera Utara. Ritual Obiyemmerupakan kegiatan keagamaan bagi etnis Tamil Hindu. Ritual Obiyemsudah ada sejak zaman Bharatayudha. Ritual ini dipercaya bisa menghapuskan karma buruk bagi siapapun yang ikut serta dan melakukan ritual ini. Ritual ini juga mewajibkan para jemaah untuk memberikan persembahan kepada para dewa dan dewi sebagai bentuk terima kasih karena sudah memberi kelimpahan, memelihara dan menjaga alam semesta. Dengan adanya komunikasi ritual masyarakat etnis Tamil Hindu di Medan dapat berkomunikasi dan berhubungan dengan sang pencipta melalui ritual Obiyem. Ritual ini masih dilaksanakan oleh masyarakat etnis Tamil Hindu sampai saat ini. Penelitian ini ingin mengetahui bagaimana  komunikasi ritual Obiyempada etnis Tamil Hindu di kota Medan dan apa saja persiapan yang dibutuhkan pada saat ritual Obiyem dilakukan. Teori yang digunakan dalam penelitian ini adalah teori komunikasi, komunikasi ritual dan komunikasi transendental. Penelitian ini menggunakan metode fenomenologi dengan pendekatan deskriptif kualitatif. Data diperoleh dari hasil wawancara mendalam dengan narasumber yang mengetahui ritual Obiyem. Kesimpulan dari penelitian ini adalah ritual Obiyemmerupakan media yang digunakan untuk berkomunikasi antara manusia dan sang pencipta untuk menghapuskan karma buruk. Komunikasi ritual ini juga dilakukan untuk mempererat hubungan masyarakat etnis Tamil Hindu.